Impacts of small-scale fisheries on mangrove fish assemblages. (4th October 2018) - Reis-Filho, José Amorim; Harvey, Euan S; Giarrizzo, Tommaso
Abstract: The data requirements and resources needed to develop effective indicators of fishing impacts on target stocks may often be great, especially for mangrove fisheries where, for example, tidal cycles sequentially flood and drain the habitat as a result of natural processes. Here, we used underwater video systems to evaluate the impact of small-scale fisheries on mangrove fish assemblages at four levels of fishing pressure (low, medium, high, and no pressure). The lowest values of species richness and abundance were recorded in the areas fished most intensively. Conversely, the highest species richness and the occurrence of larger-bodied fish were recorded in areas of reduced fishing activity, which was surprisingly similar to the "no fishing" areas. The slopes of the community size spectra steepened in response to exploitation, while the relative abundance of medium-sized fish (16–25 cm) declined. Fishing for local or regional markets, rather than subsistence, also led to a decrease in the abundance of larger fish (>41 cm). The marked response of population parameters to fishing pressure reflected the impact of unregulated small-scale fisheries on areas of mangroves. Fishery management practices that ignore contemporary changes in these environments are likely to overestimate long-term yields, leading to overfishing. Thus, size-based approaches to evaluating fishing pressure were suitable for detecting negative responses from the mangrove fish assemblages. A next step will be to integrate size- and species-based ecological approaches that provide mechanisms to address pronounced decreases in specific species as a more profitable indicator of fishing impacts on mangrove fish assemblages. This approach will allow the development of effective conservation and management strategies.